Раскопки Юхновского городища Бужанка І в 2009 г. - Каравайко, Д.В. (Археологічні дослідження в Україні, 2010)
The research of the monuments of Yukhnivka culture at the territory of Ukraine have been recommenced since 2002. Here the results of the recent excavation season at Buzhanka I hillfort are presented. The materials obtained significantly supplement our knowledge about the final stage of Yukhnivka culture.